2008
DOI: 10.1111/j.1742-4658.2008.06585.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular modeling and functional characterization of the monomeric primase–polymerase domain from the Sulfolobus solfataricus plasmid pIT3

Abstract: In all cell types, chromosomal DNA replication is a complex process entailing three enzymatic activities: helicase activity for double-helix unzipping and primase and DNA polymerase for RNA primer de novo synthesizing and elongation respectively [1,2].Based on the biochemical data accumulated to date, archaeal DNA replication involves a smaller number of polypeptides at each stage of the process and is thus just a simpler form of the much more complex eukaryotic replication machinery [3][4][5][6]. Nonetheless,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Inspection of the smaller islands revealed yet uncharacterized putative elements that encode a protein (arCOG07809, e.g., Mpal_2033 from Methanosphaerula palustris ) distantly related to the primase-polymerase (prim-pol) domains of replication proteins from plasmids of Sulfolobus (Lipps 2011; Prato et al 2008) and Thermococcus (Gill et al 2014; Krupovic et al 2013) as well as certain bacterial viruses (Halgasova et al 2012). All these proteins are members of the large superfamily of archaeao-eukaryotic primases (AEP) which also includes the catalytic subunit of the archaeal and eukaryotic primases, the enzymes responsible for the initiation of DNA replication (Iyer et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Inspection of the smaller islands revealed yet uncharacterized putative elements that encode a protein (arCOG07809, e.g., Mpal_2033 from Methanosphaerula palustris ) distantly related to the primase-polymerase (prim-pol) domains of replication proteins from plasmids of Sulfolobus (Lipps 2011; Prato et al 2008) and Thermococcus (Gill et al 2014; Krupovic et al 2013) as well as certain bacterial viruses (Halgasova et al 2012). All these proteins are members of the large superfamily of archaeao-eukaryotic primases (AEP) which also includes the catalytic subunit of the archaeal and eukaryotic primases, the enzymes responsible for the initiation of DNA replication (Iyer et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Like the heterodimeric DNA polymerase/primase of S. solfataricus (28,29) and the monomeric primase–polymerase domain encoded by the plasmid pIT3 from S. solfataricus strain IT3 (30), PolpTN2 displayed terminal transferase activity. To characterize in more detail this activity, we used two different types of primer-templates, i.e single-stranded DNA and blunt double-stranded DNA, in the presence of Mg 2+ (Figure 6A and B) (see Materials and Methods for details).…”
Section: Resultsmentioning
confidence: 99%
“…One of the main limitations of this approach is the expression of heterologous genes in E. coli (Gabor et al 2004). Although the commonly used E.coli strains have relaxed requirements for promoter recognition and translation initiation, in this host proteins may not fold correctly and many genes from extremophilic environmental samples are not translated efficiently, especially those belonging to archaea, which might show a codon usage bias (Prato et al 2008). Alternative hosts and broad-host-range vectors may be required to overcome these limitations (Angelov et al 2009;Cheng et al 2014).…”
Section: Functional Metagenomicsmentioning
confidence: 99%
“…In addition, viral metagenomics and genomics of cultured viruses has also revealed that a large proportion of predicted archaeal viral genes are 'unknown' or 'hypothetical' (Contursi et al 2014a;Prato et al 2008) expanding the content of genetic information referred as biological 'dark matter' (Martinez-Garcia et al 2014). It is expected that the annotation of additional sequenced genomes as well as the exploitation of bioinformatics tools based on structural protein homologies will help to disclose this unexplored repository of viral genes (Fig.…”
Section: Viral Metagenomicsmentioning
confidence: 99%